The dismantling of renewable energy policy in Italy. Issue 7 (10th November 2021) - Prontera, Andrea
ABSTRACT: The expansion of renewables is still dependent on appropriate policy support. Nonetheless, in the wake of the economic crisis, even pioneer European countries have begun to dismantle the set of measures implemented in the past decades. Policy dismantling in the area of renewable energy is a recent phenomenon that has attracted little attention in comparison to the study of the diffusion of support schemes. By focusing on the dismantling of renewable energy policy in Italy, this contribution helps fill this gap and highlights an important aspect of the current politics of energy transition. It shows how interactions between the political economy of the renewable energy sector, policy design, institutional constraints and external events affect policy dismantling. It also demonstrates the role of self-undermining mechanisms and framing effects in the dismantling of renewable energy policy.